FAKTOR-FAKTOR PENENTU CORPORATE SOCIAL RESPONSIBILITY (CSR) PT COCA COLA TIRTA LINA BOTTLING MENGWI BADUNG BALI - I Gusti Ayu Intan Saputra Rini; Ni Luh Gede Rusmina Dewi; Anak Agung Ayu Erna Trisnadewi (KRISNA: Kumpulan Riset Akuntansi, 2022)
The aims of this study are: (1) To prove empirically the effect of Corporate Social Responsibility (CSR) on the company's image at PT Coca Cola Tirta Lina Bottling Mengwi Badung. (2) Knowing the factors that shape Corporate Social Responsibility (CSR) at PT Coca Cola Tirta Lina Bottling Mengwi Badung. The sampling technique used was purposive sampling technique, in which the number of samples determined based on the Slovin formula, recorded as many as 98 people spread into three banjars. The data analysis technique used is simple linear regression analysis and factor analysis. The results showed that: (1) Corporate Social Responsibility (CSR) had a positive effect on corporate image at PT Coca Cola Tirta Lina Bottling Mengwi Badung. (2) Community support, diversity, environment, and product form or measure the construct of Corporate Social Responsibility (CSR). The dimension that gives the biggest contribution or the strongest as the shaper or measure of the construct of Corporate Social Responsibility (CSR) is the product.